Clinical proteomics and breast cancer. Issue 5 (October 2015) - Zeidan, Bashar A.; Townsend, Paul A.; Garbis, Spiros D.; Copson, Ellen; Cutress, Ramsey I.
Abstract Background Breast cancer is a heterogeneous disease. Yet, many molecular players and mechanisms behind the complexity of its clinical behaviour remain unknown, and advances in biomedical research are expected to unravel novel molecular discoveries in breast and other cancers. Clinical proteomics is currently experiencing rapid advances in technology that promise new means to improve breast cancer early diagnosis, stratification, and treatment response. Methods We reviewed recent literature adopting clinical proteomics in breast cancer research. Findings This review highlights the principles, advantages, limitations, discoveries and future prospects of recent clinical proteomics discovery efforts in breast cancer research. Conclusion Numerous proteomic studies of breast cancer have been accomplished aiming to aid the development of personalised therapies, increase understanding of post treatment relapse, and help improve prediction of patient prognosis. This has led to the possible identification of profiles refining breast cancer subtypes and the discovery of novel biomarkers pointing towards diagnostic and prognostic potential.